2022
DOI: 10.1242/dmm.049437
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel zebrafish model of SPEG-related centronuclear myopathy

Abstract: Centronuclear myopathy (CNM) is a congenital neuromuscular disorder caused by pathogenic variation in genes associated with membrane trafficking and excitation-contraction coupling (ECC). Bi-allelic autosomal recessive mutations in striated muscle enriched protein kinase (SPEG) account for a subset of CNM patients. Previous research has been limited by the perinatal lethality of constitutive Speg knockout mice. Thus, the precise biological role of SPEG in developing skeletal muscle remains unknown. To address … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 69 publications
2
4
0
Order By: Relevance
“…A previous study has reported the colocalization of SPEG and RyR1 in zebrafish myofibres, indicating a potential interaction between the two proteins. 33 Here, we confirm their interaction using co-IP (Figure 1E). RyR1 is part of the myospryn complex, and it was noted to be decreased in SPEG-deficient mice, but the reduction was not statistically significant (Figure 2E).…”
Section: Speg Phosphorylates S2902 Residue Of Ryr1supporting
confidence: 67%
“…A previous study has reported the colocalization of SPEG and RyR1 in zebrafish myofibres, indicating a potential interaction between the two proteins. 33 Here, we confirm their interaction using co-IP (Figure 1E). RyR1 is part of the myospryn complex, and it was noted to be decreased in SPEG-deficient mice, but the reduction was not statistically significant (Figure 2E).…”
Section: Speg Phosphorylates S2902 Residue Of Ryr1supporting
confidence: 67%
“…Animal models are the gold standard for gaining pre-clinical insights into various diseases, due to their anatomical and morphological resemblance to humans 66 . Of late, modeling of human myopathies is achieved by knocking out disease-causing genes by CRISPR/Cas9 technology 67 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, downregulation of dynamin 2 by gene silencing tunes its relative amount for BIN1 protein resulting in normal survival, muscular force and triad structures [ 34 , 129 ]. In zebrafish, knockout of a CNM causal gene SPEG (striated preferentially expressed protein kinase) that encodes a myosin light chain kinase family protein show T-tubule abnormalities with the increased expression level of dynamin 2 protein [ 130 ]. Since SPEG has been shown to interact with MTM1 [ 5 ], SPEG may regulate dynamin 2 function together with MTM1 and BIN1 in skeletal muscle.…”
Section: Dynamin: a Membrane Fission Catalyser In Endocytosismentioning
confidence: 99%